HOOK ON TO THE FIGURE (A strategy to the Teaching of Narrative Essay Writing) - Binte Ali, Fawziyah (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract We experience amusement, the sublime, sorrow, joy, pleasure, and awe in our ordinary life. These are the starting point for aesthetics, the starting point for reflecting on the nature, the value, and the quality of our experiences of the natural and constructed environments and of various aspects of ordinary life. This has led to the theme of this research study â To empower studentsâ Narrative Essay Writing skills using Malay Language with a view that they put their experiences in words and associated them with ideas of creativity and contrasted with reason and logic. This research study responds to this challenge by doing three things. First, it adopts the âMaking Thinking Visibleâ approach by Ritchhart (2011) as the main framework for the derived Narrative Essay Writing programme in this study. Second, it uses the thinking routine of âSee-Think-Wonderâ for students to experience in a multitude of ways for a given object, event, or a series of events. Third, it incorporates my personal teaching strategies on how to induce richness in narrative writing by ensuring students include âSeeâ, âHearâ, âSmellâ, Tasteâ, âFeelâ, âThinkâ and use âmetaphorsâ and âpoemsâ in their writing. Finally, experiences and knowledge gained for teaching ânarrative essay writingâ are described as a series of five action research cycles with a view to show other fellow teachers what it would be like in their class with their students.Keywords: Making Thinking Visible (MTV), Thinking Routines, See-Think-Wonder (STW)